2018
DOI: 10.1002/ece3.4476
|View full text |Cite
|
Sign up to set email alerts
|

Out of sight of wind turbines—Reindeer response to wind farms in operation

Abstract: To meet the expanding land use required for wind energy development, a better understanding of the effects on terrestrial animals’ responses to such development is required. Using GPS‐data from 50 freely ranging female reindeer (Rangifer tarandus) in the Malå reindeer herding community, Sweden, we determined reindeer calving sites and estimated reindeer habitat selection using resource selection functions (RSF). RSFs were estimated at both second‐ (selection of home range) and third‐order (selection within hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 58 publications
1
35
1
Order By: Relevance
“…In total this 44 year observation series strengthen our previous conclusion (Reimers et al, 2007). Furthermore, it also supports more recent research (Panzacchi et al, 2013a;Bartzke et al, 2014;Colman et al, 2015;Eftestøl et al, 2016;Plante et al, 2018;Skarin et al, 2018) that power lines transecting reindeer habitats have limited effects on reindeer area use. This is contradictory to findings that linear structures such as power lines act as long-term barriers for both wild and domestic reindeer (Nellemann et al, 2001;Nellemann et al, 2003;Vistnes et al, 2004;Vistnes et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In total this 44 year observation series strengthen our previous conclusion (Reimers et al, 2007). Furthermore, it also supports more recent research (Panzacchi et al, 2013a;Bartzke et al, 2014;Colman et al, 2015;Eftestøl et al, 2016;Plante et al, 2018;Skarin et al, 2018) that power lines transecting reindeer habitats have limited effects on reindeer area use. This is contradictory to findings that linear structures such as power lines act as long-term barriers for both wild and domestic reindeer (Nellemann et al, 2001;Nellemann et al, 2003;Vistnes et al, 2004;Vistnes et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…the power lines correlate with other infrastructure/factors (Reimers & Colman, 2006;Reimers et al, 2007;Flydal et al, 2019). Furthermore, more recent studies like Plante et al (2018), Skarin et al (2018), Colman et al (2015, (Panzacchi et al, 2013a), Eftestøl et al (2016) and this study, do not find separate effects from power lines in their operational period. To our knowledge, no studies published the last 10 years have found negative effects from power lines alone.…”
Section: Discussioncontrasting
confidence: 58%
“…For example, it may be possible to determine where an animal stops to graze if locations are recorded at least every five minutes [ 98 , 99 ]. It is also possible to estimate calving sites based on two-hour data or even coarser data [ 100 , 101 ] and determine when parturition starts [ 102 ] and whether the offspring survives the first few days after birth [ 103 ]. Such information can be used to evaluate calving sites in relation to environmental factors and estimate the number of calves born and, at a later stage, calf survival.…”
Section: Positioning Technologiesmentioning
confidence: 99%
“…One example being the recent push for placing wind farms in Northern Sweden, in the Swedish part of Sápmi, the Sámi homeland, thus placing the windmills on Sámi reindeer grazing lands. Here, research has shown that the reindeer actively avoid areas in and around these wind farms and consequentially the conditions for reindeer grazing is even further impaired [13]. The issue of consistently shrinking reindeer grazing lands due to various kinds of extractivism and the resulting devastating impact on the availability of lichen that the reindeer feed on, is also further aggravated by climate change [14].…”
Section: Introductionmentioning
confidence: 99%
“…Reindeer in Sweden are semi-domesticated, migratory animals, they move with the seasons and follow specific routes, the Sámi reindeer herders follow their animals. Reindeer are very sensitive animals, when disturbed they can shy away from an area even if it is a good place for grazing [13]. In our hypothetical case the proposed wind park is placed on prime reindeer grazing land and a migratory route for the animals, the area is necessary for reindeer belonging to this particular community to graze on in the winter.…”
mentioning
confidence: 99%